4CPS-289 Analysis of antineoplastic drug contamination level in the hospital pharmacy: problem monitoring and solving. (14th March 2021) - Garau, V; Gheza, SG; Colombo, S; Cadelano, S; Tulli, M; Marcias, G; Serra, P
Abstract : Background and importance: Handling of antiblastic agents poses major health risks to healthcare workers. Apart from pharmacists, nurses and physicians, staff involved in cleaning, transport and disposal of hazardous drugs or contaminated material are also involved. Monitoring via wipe samples can be used to investigate mechanisms of release and spread and thus help identify possible sources and routes of exposure. Aim and objectives: Our aim was to evaluate the effectiveness of our decontamination procedure, to obtain objective data on contamination of operators in contact with antiblastic drugs. Material and methods: The preparation rooms have closed laminar flow hoods where drugs are reconstituted and diluted using closed circuit devices. The exposure assessment involved nine nurses and two pharmacists. Biological monitoring was performed for cyclophosphamide (CP), gemcitabine and urinary metabolite 5-fluorouracil (5-FU), alpha-fluoro-beta-alanine (FBAL) in urine at the end of the shift. Analyses were performed using UHPLC-MS/MS liquid chromatography. In parallel, environmental monitoring was carried out for the determination of 5-FU and CP on the surfaces inside and adjacent to the set-up area and on the operators, using the WIPE test and PAD test techniques, respectively, at the beginning and end of the shift. Results: Levels of urinary metabolites measured were all below their respective limits of determination (LOD). Drug contamination measured by the WIPE test was found to be slightly above the reference value of 0.1 ng/cm 2 and high contamination in the external handle of the laminar flow hood was found. The analytical results collected by the PAD test showed levels of 5-FU lower than the LOD and the presence of a trace of CP on the preparer, while significant contamination by 5-FU was found on the chest and forearm of the off-field operator. Conclusion and relevance: This study highlighted environmental contamination with a low exposure of operators limited to the preparation laboratory, but higher contamination levels were found on laboratory surfaces and on an off-field operator. Improper transport of a contaminated drug basket to a clean zone is critical. This assessment allowed us to review and update our decontamination procedure, confirmed by the subsequent environmental control. A monitoring schedule for the environment and health workers and specific training courses for the cleaning teams were proposed. References and/or acknowledgements: Sottani, et al . 2017. Conflict of interest: No conflict of interest